2003
DOI: 10.1002/dc.10340
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐needle aspiration cytology in lymphadenopathy of HIV‐positive patients

Abstract: Fine-needle aspiration cytology (FNAC) of 32 HIV-positive cases presenting with lymphadenopathy was performed to evaluate its role in this group of patients. For each case air-dried smears were stained with Leishman, hematoxylin and eosin, and Zeihl-Neelsen stains for acid fast bacilli (AFB). The results were tuberculous (TB) lymphadenopathy (15), reactive lymphadenopathy (10), acute lymphadenitis/abscess (5), and suspected malignancy (2). In seven cases of TB lymphadenitis findings were suggestive of TB since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 11 publications
1
34
0
2
Order By: Relevance
“…We found this pattern in 5.4% (2 out of 37 cases with tubercular lymphadenitis) of TB cases, a finding similar to that in other previous studies where it ranged from 4.3% Abbreviations: FNAC = fine-needle aspiration cytology; TB = tuberculosis * Western data † Indian data to 28.5% (Table 4). 6,9,11,12,16,23 The NGL pattern, with both caseation and epithelioid granulomas, is the most typical pattern of tubercular lymphadenitis. It was present in 18.9% (7 out 37 cases of tubercular lymphadenitis) of our cases; other studies have reported it in the range of 26.6% to 74% (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…We found this pattern in 5.4% (2 out of 37 cases with tubercular lymphadenitis) of TB cases, a finding similar to that in other previous studies where it ranged from 4.3% Abbreviations: FNAC = fine-needle aspiration cytology; TB = tuberculosis * Western data † Indian data to 28.5% (Table 4). 6,9,11,12,16,23 The NGL pattern, with both caseation and epithelioid granulomas, is the most typical pattern of tubercular lymphadenitis. It was present in 18.9% (7 out 37 cases of tubercular lymphadenitis) of our cases; other studies have reported it in the range of 26.6% to 74% (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…La mayoría de los trabajos sobre adenopatías en estos pacientes se ha llevado a cabo en países donde la tuberculosis es endémica (India, Brasil, Irán, Zambia y Malasia) y donde, además, el número de pacientes con sida es alto y el acceso al tratamiento antirretroviral altamente efectivo es bajo, al igual que en nuestro país (3,5,6,(13)(14)(15)(16)(17)(18)(19). A diferencia de estos estudios, en los cuales la mayoría de los ganglios estudiados se evaluaron mediante una biopsia por aspiración con aguja fina, todos los pacientes en este estudio se sometieron a biopsia por escisión de ganglio linfático.…”
Section: Discussionunclassified
“…Dadas las condiciones epidemiológicas mencionadas, era predecible que la infección más común fuera la tuberculosis (casi la mitad), lo cual coincide con los datos publicados en otras series, donde la frecuencia ha oscilado entre el 26 y el 67 % (3,6,(13)(14)(15)(16)(17)(18)(19). En un estudio en Sudáfrica, Maartens, et al, encontraron una frecuencia mucho mayor de tuberculosis (92 %) (5), diferencia que probablemente se deba a la mayor incidencia de esta enfermedad en ese país (860 casos por 100.000 habitantes, en comparación con 26 por cada 100.000 en Colombia) (20) y porque, además, en dicho estudio la población evaluada incluyó solo a pacientes con sospecha de tuberculosis y con baciloscopia de esputo negativa.…”
Section: Discussionunclassified
“…2 FNAC is a simple, inexpensive, rapid investigative procedure with minimal trauma and low complication rate. 3 The material obtained from FNA can be used for diverse group of special techniques like cyto-chemistry, bacteriological culture, immune cyto-chemistry, ultra-structural studies and molecular hybridization. 4 For determining the diagnostic accuracy of FNAC, it is a usual practice to correlate cyto-diagnosis with subsequent histopathological examination of excised biopsy specimens.…”
Section: Introductionmentioning
confidence: 99%